Lipase-catalyzed synthesis of furan-based aliphatic-aromatic biobased copolyesters: Impact of the solvent. (5th October 2021) - Bazin, Alfred; Avérous, Luc; Pollet, Eric
Graphical abstract: Highlights: CALB allows the synthesis of furan based polyesters with high aromatic content. Growing chains precipitation for high aromatic contents results in low molar masses. Improved solubility in acetophenone leads to higher Mn and thermal properties. Abstract: Enzymatic polymerization is a promising route for a greener synthesis of biobased polyesters. However, this approach is still often limited to aliphatic polyesters, which present limited properties such as low thermal resistance. In this context and till now, introduction of aromatic monomers into polyesters very often resulted in low molar mass chains. Herein, aliphatic–aromatic copolyesters based on dimethyl-2, 5-furandicarboxylate were enzymatically synthesized using immobilized Candida antarctica lipase B with a particular focus on the influence of the solvent used. Two series of poly(hexylene adipate)–co-(hexylene furanoate) and poly(butylene adipate)–co-(butylene furanoate) copolyesters were successfully synthesized in diphenyl ether, displaying high molar masses (Mn up to 19 000 g.mol −1 ) for aromatic monomer contents up to 70 and 50%, respectively. High aromatic content resulted in reduced molar masses due to a loss of solubility of the growing aromatic chains. Replacing diphenyl ether by acetophenone, which had never been used before as solvent for enzymatic synthesis of polyesters, led to significantly enhanced solubility and thus an increase in the average molar masses of poly(hexylene furanoate) and poly(butylene furanoate). The resulting polyesters showed greater thermal stability and higher Tg, offering new perspectives for expanding the potential applications of such enzymatically-produced biobased aromatic copolyesters.